The division and transfer of care responsibilities in paediatric type 1 diabetes: A qualitative study on parental perspectives. (16th February 2021) - Aalders, Jori; Hartman, Esther; Pouwer, Frans; Winterdijk, Per; van Mil, Edgar; Roeleveld‐Versteegh, Angelique; Mommertz‐Mestrum, Elke; Aanstoot, Henk‐Jan; Nefs, Giesje
Abstract: Aim: To determine which factors other than child age play a role in the division and transfer of diabetes care responsibilities between parents and children with type 1 diabetes. Design: Qualitative focus group study. Methods: Across four sites in the Netherlands, 18 parents (13 mothers) of children (9–14 years) with type 1 diabetes participated in four focus groups in 2015–2016, as part of the research project 'Whose diabetes is it anyway?'. Qualitative content analysis and the constant comparison method were used to analyse the data. Results: According to parents, the transfer process included both direct and indirect tasks, had different levels (remembering, deciding, performing), was at times a difficult and stressful process, and showed large variation between families. A large number of child, parent and context factors were identified that affected the division and transfer of diabetes care responsibilities according to parents. Both positive and negative consequences of the transfer process were described for parental and child health, behaviour and well‐being. Parental final evaluations of the division and transfer of diabetes care responsibilities appeared to be dependent on parenting values. Conclusion: How families divide and transfer diabetes care tasks appeared to be affected by a complex interplay of child, parent and context characteristics, which had an impact on several parent and child domains. Impact: Parents struggle with the right timing of transfer, which calls for more support from diabetes nurses. The identified factors can be used as input for integrating a more family‐based approach into current age‐based guidelines, to improve regular care. 摘要: 目的: 确定除儿童年龄外, 哪些因素可能对父母和患有1型糖尿病的儿童的糖尿病护理责任划分和转移产生影响。 设计: 定性焦点小组研究。 方法: 2015‐2016年间, 在荷兰境内四地展开研究, 研究对象为18名患有1型糖尿病的儿童 (9‐14岁) 的父母 (13名母亲), 共分为四个重点小组, 此类研究作为'谁患有糖尿病'研究项目的一部分。此外, 采用定性含量分析法和持续比较法对数据进行分析。 结果: 父母表示, 转移过程中, 需执行不同难度的直接和间接任务 (记忆、决定、执行), 部分情况下, 面临较大困难和压力, 并且, 不同家庭的差异较大。经确定, 大量儿童、父母和背景因素可能对糖尿病护理责任的划分和转移造成影响。现已对转移过程对父母和儿童健康、行为和幸福的积极和消极后果进行描述。父母对糖尿病护理责任划分和转移的最终评估取决于其价值观。 结论: 家庭分配和转移糖尿病护理责任的方式似乎与儿童、父母及背景特征的复杂作用相关, 而此类作用对父母和儿童均有一定程度的影响。 影响: 父母忙于确定准确的转移时间, 因此, 糖尿病护士需予以更多支持。可考虑此类已确定的因素, 以便将更多家庭方法整合至现有基于年龄的指南中, 从而改善常规护理。